Attainment versus maintenance goals: Perceived difficulty and impact on goal choice - Chattopadhyay, Amitava; Chakravarti, Dipankar; Stamatogiannakis, Antonios (Elsevier, 2018)
We argue that individuals monitor and evaluate attainment and maintenance goals differently. Attainment goals feature a salient current-end state discrepancy that is processed more than the corresponding match for maintenance goals. For maintenance goals, for which a salient discrepancy is absent, contextual influences on goal success/failure receive more processing than for attainment goals. Thus, objectively more difficult attainment goals may be judged as easier than maintenance goals, when they feature sufficiently small discrepancies, or when context information is unfavorable. Study 1 establishes this core effect. Study 2 shows that thought listings capturing the relative processing of the current-end state discrepancy (match) and context information mediate perceived goal difficulty. Study 3 shows that the favorability of context information moderates the effect. Study 4 establishes joint difficulty evaluations as a boundary condition. Studies 5 and 6 (and Appendix B) show that such goal difficulty judgments affect consequential goal choices in real-world financial, workplace, and shopping situations.
Keywords: Maintenance goals;Attainment goals;Goal monitoring;Goal difficulty;Goal choice; Maintenance goals; Attainment goals; Goal monitoring; Goal difficulty; Goal choice; ODS 8 - Trabajo decente y crecimiento económico